PAI Teacher Innovation in Learning in the Era of Digital Technology for the Development of Student Interests and Talents - Zuliana, Zuliana; Qorib, Muhammad; JF, Nurul Zahriani (Journal of International Conference Proceedings, 2023)
The utilization of technology in the learning process of Islamic education becomes interesting and keeps up with developments. Seeing the emergence of thoughts from one of the community leaders who think that Islamic religious education is not needed in school learning and should be abolished from the education curriculum makes us realize how weak the awareness among the wider community that Islamic Religious Education itself is very important and has a big role in the development of the country and future state leaders. The purpose of the study was to describe the innovation of Islamic Religious Education Teachers in learning in the digital era in developing students' interests and talents with descriptive qualitative methods collected through relevant research journals. It is concluded that PAI teachers can maximize learning with existing online media. By innovating learning in order to realize an increase in interest and talent by following and exploring PAI lessons at school, madrasah, and college by realizing interesting learning (joyful learning), interactive and cooperative. PAI teachers must be technology literate to facilitate the administration of planning, assessment and implementation.Keywords: Islamic Education Teacher, Digital Technology Era, Interest and Talent, Learning